Global Value Chain in East Asia Under New Normal: Ideology- Technology-Institution Nexus - Byung-il Choi (East Asian Economic Review (EAER), 2020)
This paper analyzes how the current Global Value Chain (GVC) of East Asia has been established, and attempts to project the future trajectory of GVC under New Normal in the global trading system. For this purpose, the framework of Ideology-TechnologyInstitution nexus is presented with focus on the dynamics of interplay between ideology and technology, duly recognizing the dual-aspect of technology- a platform for business and also for national defense. The paper analyzes how the Information and Communication Technology (ICT) of the 1990s played a role of "facilitator" in shaping the GVC of East Asia, where China plays 'factory for final assembly' and the US plays 'the largest consumer'. Under New Normal, digital technology is likely to play the opposite role of "disrupting" the GVC of East Asia, unlike ICT. The paper explores the mechanism behind this great disruption. What is driving New Normal is the US-China power competition, seeking for dominance in East Asia and beyond. This paper argues that New Normal is not temporary shock, but will last for some time. Under this presumption, the paper presents three scenarios for the future trajectory of GVC in East Asia.
Keywords: F13; F51; F68; 330; Global Value Chain; East Asia; New Normal; Ideology-Technology-Institution Nexus; Dual-Aspect of Technology; Trade-Security Nexus